Thailand Agromyzidae (Diptera)—2 - Sasakawa, Mitsuhiro (Zootaxa, 2013)
The 29 species of the subfamily Agromyzinae in Thailand are revised, among these 13 species are described as new to science: Melanagromyza ancyla sp. nov., M. catalexis sp. nov., M. cirrappendicula sp. nov., M. lunulata sp. nov., M. macilenta sp. nov., M. multistriata sp. nov., M. pandiculata sp. nov., M. sexseriata sp. nov., M. spinuliloba sp. nov., M. turgida sp. nov., Ophiomyia flagellata sp. nov., O. quadrifida sp. nov., O. striata sp. nov.; and nine species (three species of Agromyza, two of Melanagromyza and four of Ophiomyia) are recorded as new to Thailand. One new synonym is established: Melanagromyza cordiophoeta Spencer, 1961, as a junior synonym of M. dolichostigma Meijere, 1922. Keys to the Thailand species of the genera Agromyza, Melanagromyza and Ophiomyia are given.